Innovation as a business success factor: Multiple case studies - Freo, Carla Cristina Conrad; Miritz, Luciane Dittgen; Moiseichyk, Ana Elizabeth; Timm, Luiz Carlos (Seven Editora, 2023)
Innovations are fundamental for organizations, in maintaining their competitive potential and in the permanence of their customer. Innovation can be classified into a few different types, according to its emergence, because the innovative process can happen in various ways, meeting the current needs of organizations and consumers. In view of the above, this work had as main objective to identify what the organizations that are installed in a city located in the south of Brazil, have as innovation, verifying the types of innovations and organizational performance. The present study was developed from a qualitative research, bibliographic analysis and a study of multiple cases. Four companies participated in the survey, through semi-structured interviews, in which it was found that the main reason to invest in innovation is the search for consumer satisfaction. Companies seek to innovate to gain space, make profits and maintain their permanence in the market through the satisfaction of their customers. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-153